Clonidine-Activation of Epileptic Foci - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
The effects of clonidine, an adrenergic a2 agonist hypotensive agent, and methoxital, a short-acting barbiturate anesthetic, on epileptiform discharges detected by presurgical magnetoencephalography (MEG) were investigated in 14 patients with medically intractable focal epilepsies treated at the University of Erlangen-Nuernberg, Germany.